PENGGUNAAN KALPIN TERHADAP PENINGKATAN PENGETAHUAN TENTANG DIET DAN ASUPAN MAKANAN PENDERITA DIABETES MELITUS - Bar, Arvida. (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
DM disease greatly affects the quality of human resources and has an impact on increasing health costs which are quite large. Many people do not realize the importance of controlling blood sugar levels in diabetics are not even aware that they have diabetes, and realize after the occurrence of complications of the disease themselves. The purpose of this study was to determine the effect of using a smart calendar on increasing the knowledge of DM patients at the Penyengat Olak Health Center, Muaro Jambi Regency. The design used was a case-control with a quasi-experimental design, using a pretest-posttest approach with a control group, with a total sample of 30 which was divided into 15 intervention groups and 15 control groups. Data analysis used t-test and independent t-test. Statistical analysis found that there was an effect of smart calendars with knowledge about diet and food intake management in DM patients, with a p-value of 0.004, so it was concluded that the use of SMART CALENDAR as a reminder medium for sufferers could increase their knowledge, improve their discipline to manage food so that in the end is expected to reduce blood sugar levels of respondents before and after the intervention. By comparing the control group, p.value = 0.011, it can be concluded that there is a significant difference in the average group of respondents who use the SMART CALENDAR and those who do not use the SMART CALENDAR. In conclusion, the use of a PINTAR CALENDER can help increase knowledge about diet and food management but must be accompanied by the supervision of officers or families.